Digital Information and Provision of E-Resources and its Services in Engineering Colleges - M, Krishnamurthy; Reddy B, Subhash; E, Roopa (International Journal of Information Studies, 2025)
This study presents the survey results obtained from 150 professionals employed at various engineering colleges in Karnataka, India, with an aim to understand the efforts of information users in traveling extra miles to accomplish the information needs of the generation Z. It describes the initiatives, efforts, arrangements, and work carried out by information users in the provision of access to e-Resources and also examines barriers in extending e-Resource services. Findings reveal that majority of the information users are providing digital services in spite of lack of support from their management and subsequently lack of demand from the user.